Lactonase-mediated inhibition of quorum sensing largely alters phenotypes, proteome, and antimicrobial activities in Burkholderia thailandensis E264 - Gonzales, Mélanie; Plener, Laure; Armengaud, Jean; Armstrong, Nicholas; Chabrière, Éric; Daudé, David (Frontiers in Cellular and Infection Microbiology, 2023)
Burkholderia thailandensis is a study model for Burkholderia pseudomallei, a highly virulent pathogen, known to be the causative agent of melioidosis and a potential bioterrorism agent. These two bacteria use an AHL-mediated quorum sensing (QS) system to regulate different behaviors including biofilm formation, secondary metabolites, and motility. Using an enzyme-mediated quorum quenching (QQ) strategy, based on the lactonase SsoPox, we evaluated the importance of QS in B. thailandensis. By combining proteomic and phenotypic analyses, we demonstrated that QS disruption largely affects overall bacterial behavior including motility, proteolytic activity, and antimicrobial molecule production. We further showed that QQ treatment drastically decreases the bactericidal effect against two bacteria (Chromobacterium violaceum and Staphylococcus aureus), while a spectacular increase in antifungal effect was observed against fungi and yeast (Aspergillus niger, Fusarium graminearum and Saccharomyces cerevisiae). This study provides evidence that QS is of prime interest when it comes to understanding the virulence of Burkholderia species and developing alternative treatments.